PENINGKATAN PRODUKTIVITAS DAN KUALITAS PADA LINI PRODUKSI DRUM MENGGUNAKAN PENDEKATAN LEAN SIX SIGMA - Yoseph; Kosasih, Wilson; Doaly, Carla Olivia (Universitas Tarumanagara, 2023)
The high number of product defects in the manufacturing industry has a significant impact on the products quality and productivity of the enterprise. The research was conducted at manufacturing companies that produce drums, pail cans, and other can packaging. In the production process, they found a high defect rate in the drum production process, which resulted in a decrease in the quality and productivity of the factory. This research is aimed at assisting companies in reducing the defect rate of drum production; improving process efficiency; providing proposed process improvements; and minimizing existing waste. This study used the Lean Six Sigma approach, using SIPOC and CTQ to define problems, and measure process efficiency and product quality, obtaining a process cycle efficiency value of 8.06% and a sigma value of 4.6%. Based on the pareto diagram, the dominant defects are abrasions, paint top/body damaged, and screen printing top/body damaged, while based on WAM, the dominant defects are defects, inventory, and waiting. Based on this stage, analysis was carried out on all three defects using fault tree analysis, why-why analysis, and FMEA. In the future, improvements will be implemented to reduce the number of defects and increase productivity so that there is an increase in the value of PCE of 9.23% and a sigma value of 5.04 after improvements.